Cashless Payment System Model at the Ministry of Cooperatives and Small and Medium Enterprises - Cheria Puspita, Galih; Nur Afsdy Saksono, Rochmad; Karunia, Luki (Pusat Publikasi Nusantara, 2023)
To encourage the creation of effective and efficient APBN implementation, widely known by the public, and accountable, the payment mechanism in the APBN implementation process must be simplified but modern with the use of information technology that is increasingly optimal. One of the efforts made is to change shopping behavior, especially related to the use of the Money Supply mechanism which gradually shifts from fully using cash funds to cashless systems through the implementation of digital payments such as Government Credit Cards (KKP) and Cash Management System Virtual Accounts (CMS VA). This study aims to explore the factors that cause the low implementation of Cashless payment systems in the form of KKP and CMS VA within the Ministry of Cooperatives and SMEs, and find a model that can optimize it. Researchers use a qualitative approach with the case study method because they try to focus intensively on a particular object that studies it as a case, and cannot be generalized because the results of this study only apply to the case being studied. The results of this study show that leadership commitment is the factor that most influences the implementation of the cashless payment system, and also determines the influence of other factors such as human resource factors, the availability of SOPs, reward and punishment mechanisms, and the involvement of the Bank in the use of KKP and CMS VA. Satker must synergize with other parties so that in every stage of implementation starting from the signing stage of cooperation between Satker and the Bank, issuance and delivery of instruments, use transactions and accountability, until the supervision and monitoring evaluation stage can run better so that it can have an optimal impact on the implementation of Cashless payment systems within the Ministry of Cooperatives and SMEs